Disrupting the rent-a-car market through sharing economies - Garcia, Bruno Mendes Pinheiro (2016)
The World is changing. As Tom Goodwin, Senior Vice President of Strategy and Innovation at Havas Media, would eloquently put it: “Uber, the world’s largest taxi company, owns no vehicles. Facebook, the world’s most popular media owner, creates no content… And Airbnb, the world’s largest accommodation provider, owns no real estate”. In that line of thought “Disrupting the Rent-a-Car Market Through Sharing Economies” is a Directed Research Work Project with the purpose of building a Business Plan for launching a Mobile Peer-to-Peer Car Rental Platform in Portugal, while creating Consumer Value and driving sustainable competitive advantage.